The relationship between remnant cholesterol and WHO grade of pancreatic neuroendocrine neoplasms - Zhou, Hao; Wang, Yu; Liu, Yongkang; Guo, Chuangen; Wang, Jianhua; Chen, Xiao (Frontiers in Endocrinology, 2025)
BackgroundCholesterol plays a role in tumorigenesis. However, the association between remnant cholesterol and pancreatic neuroendocrine neoplasms (PNENs) has not been clarified. In the present study, we explored the association between the remnant cholesterol level and the World Organization Health Grade of PNENs.MethodsThe clinical and histopathological characteristics of PNEN patients who underwent surgery at our institution were retrospectively analyzed. Remnant cholesterol was calculated as total cholesterol - high-density lipoprotein cholesterol+low-density lipoprotein cholesterol. The remnant cholesterol/cholesterol ratio was also calculated. Grade 3 PNENs and pancreatic neuroendocrine carcinoma (PNEC) were defined as high-grade PNENs. The relationship between remnant cholesterol or the remnant cholesterol/cholesterol ratio and PNENs was analyzed using multivariable logistic regression analysis.ResultsPatients with high-grade PNENs had higher remnant cholesterol levels and remnant cholesterol/cholesterol ratios than did those with low- and moderate-grade PNENs (P < 0.01). High proportions of patients with a remnant cholesterol concentration > 1.2 and a remnant cholesterol/cholesterol ratio > 0.26 were observed in patients with high-grade PNENs compared to those with low and moderate PNENs (27.74% vs 9.27%, P = 0.02; 19.56% vs 7.28%, P = 0.016). Multivariate logistic regression analysis revealed that remnant cholesterol was associated with high-grade PNENs (odds ratio (OR) =2.41, 95% confidence interval (CI): 1.28 - 4.56). Similar associations were observed between high-grade PNENs and a remnant cholesterol concentration greater than 1.2 (OR = 3.34, 95% CI: 1.15 - 9.68). High-grade PNENs were also associated with the remnant cholesterol/cholesterol ratio (OR = 1.45, 95% CI: 1.06 - 2.02, for continuous data; OR = 4.00, 95% CI: 1.32 - 12.09, for cholesterol/cholesterol ratio > 0.26). Similar associations were observed between the remnant cholesterol level and the remnant cholesterol/cholesterol ratio and PNEC.ConclusionsA high remnant cholesterol level and a high remnant cholesterol/cholesterol ratio were associated with high-grade PNENs or PNECs.